2016
DOI: 10.4172/2169-0286.1000119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Personality Type on Job Productivity

Abstract: The objective of this research is to find out the impact of personality type of an employee on his job productivity. A survey of 10,000 individuals was conducted from different cities to elucidate the associations between organizational goals and a number of intra-organizational variables. In this research, author found that there are many factors which affect the employee performance and which are either affected by employee's performance or employee's performance is affected by them. Among those factors, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Productivity is the ratio of input-output in time with consideration of quality (Najam us Sahar, 2016). Another opinion says Productivity is a concept that describes the relationship between results (number of goods or services), number of sources (number of labor, capital, land, energy, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Productivity is the ratio of input-output in time with consideration of quality (Najam us Sahar, 2016). Another opinion says Productivity is a concept that describes the relationship between results (number of goods or services), number of sources (number of labor, capital, land, energy, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Other research found that generally, personality had an affected on employee job performance [40]. There is a positive relationship between Employee Productivity and explanatory variables like Agreeableness, Consciousness, and extraversion [41]. In our study, the magnitude of direct influence personality on performance is 5.02 % meaning that the contribution of personality has affected performance is small.…”
Section: Discussionmentioning
confidence: 40%
“…In North Central States, there is little or no statistical data to reveal the existence and extent of occupational stress influence on productivity especially among workers in (Emotional Intelligence As A Predictor Of Productivity And Occupational Stress Of Employees …) electrical occupation. There is a sharp decline in performance of workers in electrical related industries in North central (Najam-us-Sahar, 2016). There is also a problem of high worker burn-out, massive alcohol consumption, high morbidity and mortality rates in the recent years (Ministry of Environment, 2013) which suggest excessive and prolonged stress.…”
Section: Literature Reviewmentioning
confidence: 99%